Inhibition of histone acetyltransferase function radiosensitizes CREBBP/EP300 mutants via repression of homologous recombination, potentially targeting a gain of function - Manish Kumar (Nature Portfolio, 2021)
Mutations in histone acetyltransferases (HATs) CREBBP and EP300 are generally thought to lead to decreased function or absence of protein product. Here the authors describe a gain of function of several CREBBP mutations leading to baseline hyper-acetylation, increased homologous recombination and potential synergy between radiation and HAT inhibition in CREBBP/EP300 mutant tumors.